The German Supply Chain Act – A Sustainable Regulatory Framework for Internationally Active Market Players? - Mittwoch, Anne-Christin; Bremenkamp, Fernanda Luisa (Review of European and Comparative Law, 2023)
On January 1, 2023, the German Act on Corporate Due Diligence in Supply Chains (LkSG) entered into force. It is the most important step taken so far by the German legislature in terms of promoting corporate sustainability and protecting human rights in globalized supply chains. Unfortunately, however, it did not make use of the opportunity to take on a pioneering role in the broader comparative context. The authors conduct a critical analysis of the sustainability concept of the Act, as well as its provisions on scope and enforcement. In both aspects, the Act falls short of expectations; it does not introduce a comprehensive concept of sustainability, small and medium-sized enterprises are excluded from the scope of application, and comprehensive due diligence along the supply chain is not achieved. On the enforcement level, the main weakness of the LkSG lies in its exclusion of civil liability.